Meningkatkan hunian hotel dan kepuasan pelanggan melalui strategi reservasi online yang efisien dan inovatif - Krisnayanti, Si Luh Made; Armoni, Ni Luh Eka; Darlina, Lien; Mandang, Selvie Ratna Ivone (Journal of Commerce, Management, and Tourism Studies, 2022)
This study aims to evaluate the contribution of online and offline room reservation methods to overall room occupancy at LINK Hotel, while also examining the implementation of an online reservation system. The primary objective is to determine how these reservation channels influence occupancy rates and to identify the benefits and challenges associated with online reservations. Data were collected using multiple methods, including observation, in-depth interviews, documentation, and a review of relevant literature. This multi-method approach provided a comprehensive understanding of the current reservation practices and their impact on hotel occupancy. The study analyzed reservation data over a three-year period, using both descriptive statistical techniques and qualitative descriptive methods to capture trends and underlying factors influencing the performance of each reservation method. The results revealed significant fluctuations in the monthly contribution of offline reservations. In 2015, offline reservations contributed an average of 6.8% to room occupancy, which decreased to 1.87% in 2016 and further to 1.62% in 2017. In contrast, online reservations consistently played a dominant role in driving room occupancy, contributing 93.41% in 2015, increasing to 98.13% in 2016, and reaching 98.38% in 2017. These figures indicate that the shift towards digital booking methods has had a substantial impact on occupancy rates. Furthermore, the study explores the operational steps involved in online reservation processes, the benefits derived from leveraging digital channels—such as improved efficiency, customer convenience, and increased reach—and recommendations for optimizing the application of these systems. The findings suggest that enhancing the online reservation experience is critical for maintaining and potentially increasing room occupancy. In conclusion, the study supports the strategic shift towards online reservations, providing actionable insights for hotel management to further capitalize on digital channels to improve occupancy and customer satisfaction.